2021
DOI: 10.1093/rheumatology/keab093
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral ulcerative keratitis in rheumatoid arthritis patients taking tocilizumab: paradoxical manifestation or insufficient efficacy?

Abstract: Objectives Peripheral ulcerative keratitis (PUK) is a severe corneal condition associated with uncontrolled rheumatoid arthritis (RA). Tocilizumab (TCZ) is used to control RA, however, episodes of paradoxical ocular inflammation have been reported in TCZ-treated patients. We report a case series of PUK in TCZ-treated RA patients with ophthalmological and systemic findings and discuss the potential underlying mechanisms. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…23 Cohen reported that rare cases of PUK may occur in patients with long-standing RA after a switch to tocilizumab. 24 However, our patient had PUK before the use of tocilizumab, and her condition was gradually relieved by treatment with tocilizumab and local therapies. It is suggested that PUK can be effectively relieved by tocilizumab in some patients; however, the effect needs to be closely monitored, and the treatment plan needs to be adjusted quickly in the case of inefficacy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…23 Cohen reported that rare cases of PUK may occur in patients with long-standing RA after a switch to tocilizumab. 24 However, our patient had PUK before the use of tocilizumab, and her condition was gradually relieved by treatment with tocilizumab and local therapies. It is suggested that PUK can be effectively relieved by tocilizumab in some patients; however, the effect needs to be closely monitored, and the treatment plan needs to be adjusted quickly in the case of inefficacy.…”
Section: Discussionmentioning
confidence: 71%
“…In patients with RA and small paracentral corneal ulcerations or perforations, the application of tissue adhesive and a bandage contact lens and the introduction of topical cyclosporine may be the preferred initial treatment 23 . Cohen reported that rare cases of PUK may occur in patients with long‐standing RA after a switch to tocilizumab 24 . However, our patient had PUK before the use of tocilizumab, and her condition was gradually relieved by treatment with tocilizumab and local therapies.…”
Section: Discussionmentioning
confidence: 78%
“…38 TCZ has also shown efficacy in other refractory inflammatory diseases, including ocular diseases. [39][40][41][42][43][44][45] TCZ may be useful in PUK associated to RA. 26 Paradoxically, PUK has been described in RA patients receiving TCZ, which can be interpreted as a lack of efficacy or as a paradoxical reaction to the drug.…”
Section: Discussionmentioning
confidence: 99%